2022
DOI: 10.1108/pijpsm-05-2022-0073
|View full text |Cite
|
Sign up to set email alerts
|

Public cooperation with police in Detroit: a testing of three perspectives

Abstract: PurposeWhile public support for and cooperation with the police has been deemed vital for police effectiveness, what shapes such support and cooperation has not been fully examined. The purpose of this study is to explore three perspectives on public cooperation with police simultaneously: (1) police legitimacy, (2) legal cynicism, and (3) neighborhood norms.Design/methodology/approachThe data used in this study came from a survey conducted with 408 residents across three neighborhoods in Detroit, Michigan, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
(135 reference statements)
2
2
0
Order By: Relevance
“…(2021) are based on samples from China, a social and cultural context very different from that of the United States. This finding however echoes what Khatchatourian et al . (2022) revealed that perception of neighborhood informal social control (a key dimension of collective efficacy) does not predict cooperation after controlling for trust in police and felt obligation to obey the police.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…(2021) are based on samples from China, a social and cultural context very different from that of the United States. This finding however echoes what Khatchatourian et al . (2022) revealed that perception of neighborhood informal social control (a key dimension of collective efficacy) does not predict cooperation after controlling for trust in police and felt obligation to obey the police.…”
Section: Discussionsupporting
confidence: 91%
“…This finding however echoes what Khatchatourian et al (2022) revealed that perception of neighborhood informal social control (a key dimension of collective efficacy) does not predict cooperation after controlling for trust in police and felt obligation to obey the police. Khatchatourian et al (2022) draw upon data from the city of Detroit and include an array of predictors that this study does not examine due to a lack of measures, such as perception of police legitimacy, legal cynicism, neighborhood anti-snitch culture, contact with police and fear of crime. Our similar findings nonetheless suggest that perceived direct informal social control does not necessarily translate to a willingness to exercise indirect informal social control by reporting crime or providing crime tips to the police.…”
Section: Cooperation With the Policesupporting
confidence: 69%
See 2 more Smart Citations
“…Factors associated with willingness to cooperate with police Scholars have attempted to examine the factors associated with willingness to cooperate with police. Although not all agree, they have identified a variety of factors, including police legitimacy (Tyler, 1990(Tyler, , 2001Murphy et al, 2008;Khatchatourian et al, 2022;Sunshine and Tyler, 2003), contact experience with police (Tyler and Fagan, 2008;Schuck et al, 2008) and sociodemographic factors including age, gender and race/ethnicity.…”
Section: Literature Reviewmentioning
confidence: 99%